Old world & new world fairy tales - Williams-Ellis, Amabel 1894-; Stobbs, William (New York F. Warne, 1966)
Twenty-nine fairy tales from folklore all around the world, with notes on their specific sources and the individual stories.
Keywords: Fairy tales